Comparative evaluation of effectiveness and safety of 92% lactic acid peel versus 35% glycolic acid peel in facial melasma and its impact on melasma quality of life score - Pdiangty Giri Mawlong; Saroj Lochab; Nishant Bisht (Asian Journal of Medical Sciences, 2025)
Background: Melasma is a prevalent acquired skin hyperpigmentation condition. This condition typically manifests on the face and can considerably impair an individual’s self-image and self-esteem. Consequently, patients may find themselves avoiding social interactions due to feelings of social embarrassment. Therefore, prompt treatment of melasma is essential in enhancing patients’ self-confidence. Aims and Objectives: The objective is to evaluate the effectiveness and safety of 92% lactic acid (LA) peels in comparison to 35% glycolic acid (GA) for the treatment of melasma, as well as their impact on the quality of life related to melasma. Materials and Methods: In this research, individuals with facial melasma were randomly divided into two groups, each comprising 20 participants. They underwent treatment with either a 92% LA peel or a 35% GA peel, administered at 3-week intervals over an 18-week duration. The results were evaluated 3 weeks after the last treatment session. Assessment methods utilized, including the Melasma Area and Severity Index (MASI) scoring and Melasma Quality of Life (MELASQOL) scores, to gauge treatment outcomes in both groups. Furthermore, any adverse effects were recorded. Results: The results were statistically significant regarding the reduction in mean and percentage decrease of the MASI and MELASQOL scores in both groups when compared to baseline. However, no significant differences were observed between the two groups, and only minimal adverse effects were reported. Conclusion: Both the 92% LA peel and the 35% GA peel have been shown to be effective and safe in reducing facial melasma, as well as enhancing MELASQOL scores, with comparable results observed in both treatment groups.